An overview of the genesis, sources, manifestations and impact of Small Arms and Light Weapons (SALW) in Northern Nigeria - Sule, Babayo; Mikail, Ibrahim Kawuley; Yahaya, Muhammad Aminu (Universiti Utara Malaysia Press, 2020)
The protracted proliferation of Small Arms and Light Weapons (SALW) from around the globe to Africa, specifically in Northern Nigeria, had led to a plethora of social crises that have culminated to the insecurity across the region for more than a decade. Armed conflicts that resulted from the effects of the spread of SALW across the three geopolitical zones in the North had subsequently led to the Boko Haram insurgency in the Northeast, farmers-herders conflict in the North central, armed banditry in the Northwest, and ethnoreligious conflicts and mass kidnappings in the region. The objective of this study is a critical and thorough investigation of the SALW in exacerbating armed conflicts, in general, in the Northern part of Nigeria. The main problems identified in this study are the armed conflicts that have threatened to entirely destabilize the region, and the increased distribution of SALW across the region despite the global efforts to contain their spread for security reasons. This study used a qualitative method of data collection and analysis. Both primary and secondary sources were employed in this study. The primary sources were the interviews conducted with selected informants in the relevant area of study. The secondary sources were the use of available literature on the subject matter. Discussions were carried out by using thematic analytical interpretations. The research discovered that the rampant armed conflicts in Northern Nigeria is the reminiscent of the spread of SALW in the region, which subsequently led to the present critical security situation. Furthermore, weak policies and political institutions had contributed to the spread of SALW, indicating a need for a strong policy approach. This study recommends, among other numerous suggestions, that efforts should be intensified in intelligence gathering to detect the networking of the racketeers in the armed business and contain them appropriately, as well as total blockage of the weapons’ distribution routes.